The Routledge handbook of phenomenology and phenomenological philosophy - De Santis, Daniele 1983-; Hopkins, Burt C. 1954-; Majolino, Claudio (Routledge, Taylor & Francis Group, 2021)
"Phenomenology was one of the twentieth century's major philosophical movements, and it continues to be a vibrant and widely studied subject today with relevance beyond philosophy in areas such as medicine and cognitive sciences. The Routledge Handbook of Phenomenology and Phenomenological Philosophy is an outstanding guide and reference source to this important and fascinating topic. Comprising seventy-five chapters by a team of international contributors, the Handbook offers unparalleled coverage of the subject, and is divided into five clear parts: Phenomenology and the History of Philosophy Issues and Concepts in phnomenology Major Figures in Phenomenology Intersections Phenomenology in the World. Essential reading for students and researchers in philosophy studying phenomenology, The Routledge Handbook of Phenomenology and Phenomenological Philosophy is also suitable for those in related disciplines such as psychology, religion, literature, sociology and anthropology"--
Includes bibliographical references and index
Keywords: Phänomenologie; Phenomenology; Aufsatzsammlung